A Straightforward Approach Towards Phosphadecalones by Microwave-Assisted Diels–Alder Reaction - Elżbieta Łastawiecka; Anna E. Kozioł; K. Michał Pietrusiewicz (Molecules)
A stereoselective and scalable strategy for the synthesis of phosphorus-containing bicyclic and tricyclic compounds from 1-phenylphosphin-2-en-4-one 1-oxide is presented. This activated dienophile, available in both racemic and enantiopure forms, undergoes smooth [4+2] cycloadditions with acyclic and cyclic dienes, affording products with excellent yields and controlled stereochemistry. Notably, the cis/trans-fusion of the cycloadducts (phosphadecalones and phosphahexahydrochrysene) can be selectively controlled by fine-tuning the conditions of microwave-assisted cycloaddition reaction. The influence of temperature, time, and steric effects on cis/trans and endo/exo selectivity was examined in detail. The molecular structure, including the absolute configuration, of eight products has been determined by X-ray crystallography. These analyses further established the endo-selective nature of the cycloaddition, favoring the P=O face of the dienophile. Post-cycloaddition transformations of selected P-stereogenic phosphadecalone, such as isomerization, reduction and deoxygenation, demonstrate the synthetic versatility of the resulting products.